“He didn’t want to admit the peculiar nature of the two centuries’ boundary period”: Leonid Dolgopolov’s unpublished notes on Ivan Bunin - Vassili Molodiakov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
Russian Modernism scholar Leonid Konstantinovich Dolgolopov (1928– 1995) authored only a couple of research articles concerning Ivan Bunin, but these papers were important in the process of Bunin’s interpretation in the 1970s. Dolgopolov’s unpublished notes on Bunin from his archive, preserved by the author and donated to the Pushkin House in 2019, add a lot to his known works. Applying Tynianov’s formula “archaists and innovators”, Dolgopolov described Bunin as a “man of the nineteenth century” totally alien to the twentieth century’s literature, not only modernist one. Bunin’s rejection of contemporary literature and its subjects related to his attitude to Russian revolution, which he did not expect and which he perceived as a spontaneous revolt, not as a global social shift. Also, polemicizing with O. Mikhailov’s interpretation, Dolgopolov defined “Cornet Yelagin’s Case” (1925) as an experimental novel mainly influenced by Dostoevsky, a novelist profoundly alien to Bunin. According to Dolgopolov, it is because of Dostoevsky’s influence that artistic discoveries, made in this novel, were not further developed in the writer's work.